South African legislation pertinent to building practice: A review in the context of inherent dolomite land hazard - Ngubelanga, S.; Rooy, J.L. Van (International Journal of Environment, Agriculture and Biotechnology, 2023)
Dolomite land occurs across five of the nine South Africa provinces and its vast occurrence and distribution makes it difficult to avoid when planning for building projects. Such terrains are generally associated with the formation of ground instability events (sinkholes & subsidences) causing widespread damage to infrastructure or loss of life. Under section 24 of the Constitution of South Africa, (Act 108 of 1996), safe environment and protection thereof has been elevated to a basic human right. In the context of safe land use planning and sustainable infrastructure development, more particularly post-1994, a series of statutes have been promulgated to provide a legislated framework for building practice in South Africa. The National Building Regulations and Building Standards (Act 103 of 1977) as amended, and the current National Building Regulations (NBR’s), have been promulgated to promote uniformity in the law relating to the erection of buildings in South Africa including prioritizing safe land for human settlement. A key principles is that if conditions of the land on which a building was or is being or is to be erected, shows signs of becoming dangerous to property and/ or life, such conditions must be investigated and secured. However, there seem to be challenges in the practical implementation. This paper therefore presents a review into the legislation pertinent to building practice to identify possible gaps, implementation challenges and damaging effects due to inappropriate development of dolomite land. The research further scrutinizes an influence or lack thereof, of the technical requirements aimed at ensuring sustainable development on geologically hazard prone terrains.